2019
DOI: 10.17645/si.v7i3.2045
|View full text |Cite
|
Sign up to set email alerts
|

Vocational Education and Employment: Explaining Cohort Variations in Life Course Patterns

Abstract: A stylized finding on returns to vocational education is that vocational compared to general education generates a differential life course pattern of employability: while vocational education guarantees smooth transitions into the labour market and thus generates initial advantages, these erode with increasing age, leading to late-life reversals in employment chances. We contribute to this research by assessing cohort variations in life-cycle patterns and distinguishing two explanations for late-life reversal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 32 publications
(47 reference statements)
1
17
0
Order By: Relevance
“…Moreover, this finding indicates that less educated individuals are more likely to end up in physically demanding jobs, and as a consequence, physical health gains more importance for that particular group. This result is in line with findings from life course research (Kratz et al, 2019). Note that the effects of physical health are very small, which is not surprising, however, because in our observation window characterized by an extensive demand for qualified workers, almost everyone in our sample finds employment within six months.…”
Section: Heterogeneity Across School Degree Levelssupporting
confidence: 91%
“…Moreover, this finding indicates that less educated individuals are more likely to end up in physically demanding jobs, and as a consequence, physical health gains more importance for that particular group. This result is in line with findings from life course research (Kratz et al, 2019). Note that the effects of physical health are very small, which is not surprising, however, because in our observation window characterized by an extensive demand for qualified workers, almost everyone in our sample finds employment within six months.…”
Section: Heterogeneity Across School Degree Levelssupporting
confidence: 91%
“…In a similar vein, educational attainment in adulthood and the concomitant labour market outcomes are related to individuals' social background and occupational status (Bratsberg et al, 2019;Luchinskaya & Dickinson, 2019). Last but not least, two cohort comparisons provide the first tentative evidence that the relationship between types of education and labour market outcomes may have changed over time (Glauser et al, 2019;Kratz et al, 2019). However, the reasons are difficult to pinpoint with the available data.…”
Section: Discussionmentioning
confidence: 99%
“…Employment is also the focus of Kratz, Patzina, Kleinert and Dietrich's (2019) contribution. It analyses changes in employment patterns of workers with general and vocational education across cohorts.…”
Section: Aim Of and Contributions To The Thematic Issuementioning
confidence: 99%
“…On the other side, despite advantage of VET graduates in employment and income at beginning, losing of their skills or negative effects of difficulties which they can experience in meeting recently arising skills in their life-time employment came to the fore in recent studies (Hanushek et al, 2017;Kratz et al, 2019). In this context, Hanushek et al (2017) first studied the lifetime returns to vocational versus general education by investigating the employment status and income of both vocational and general education graduates, and found that VET graduates have the advantage in employability and income levels immediately after graduation.…”
Section: Skill Mismatch Field-of-study Mismatch and Penaltymentioning
confidence: 99%
“…When the VET is offered in such an occupation-specific way as in Germany, it seems that there exists a trade-off over the lifetime returns. Kratz et al (2019) attempted to provide more insight into this trade-off based on cohort variations in life course patterns. They found that the advantage of VET graduates is more pronounced across cohorts at younger ages.…”
Section: Skill Mismatch Field-of-study Mismatch and Penaltymentioning
confidence: 99%